In vitro control of phytopathogenic fungi and damping-off of tomato by Bacillus velezensis LABIM40 (CMRP 4489) - Paula Sanches de Almeida; Julia Pezarini Baptista; Allan Yukio Higashi; Gustavo Manoel Teixeira; Luiz Henrique Campos de Almeida; Admilton Gonçalves de Oliveira Junior; Maria Isabel Balbi-Peña (Semina: Ciências Agrárias, 2023)
The in vitro antagonistic activity of Bacillus velezensis LABIM40 (strain CMRP 4489) was assessed against Alternaria linariae, Botryotinia squamosa, Colletotrichum lindemuthianum, Gibberella zeae, and Rhizoctonia solani. An experiment was conducted using treated seeds under growth chamber conditions to determine the impact of various LABIM40 formulations on tomato seedling growth and the biocontrol of damping-off caused by R. solani. The treatments included the use of LABIM40 cell suspension, LABIM40 cell-free supernatant (CFS), 10 times concentrated CFS (10× CFS), commercial products based on Bacillus amyloliquefaciens (CP_1) and Bacillus subtilis (CP_2), and water. The effects of these products were assessed on tomato seedlings grown in sterile substrate or substrate inoculated with R. solani. In a dual culture test, B. velezensis LABIM40 inhibited the mycelial growth of the aforementioned fungal pathogens by 46.6%, 67.4%, 64.7%, 49.0%, and 54.4%, respectively. The minimum inhibitory concentration against each fungus was determined using varying concentrations of CFS in potato dextrose agar medium, followed by a regression analysis of mycelial growth inhibition. Except for A. linariae, the logarithmic model provided the best fit in all cases. Tomato seedlings from seeds treated with 10× CFS in inoculated substrate exhibited a survival rate 57% higher than that exhibited by the control treatment. However, no growth promotion was observed in tomato plants from seeds treated with LABIM40 cells or its CFS metabolites. In summary, these findings highlight the antagonistic activity of B. velezensis LABIM40 against A. linariae, B. squamosa, C. lindemuthianum, G. zeae, and R. solani, as demonstrated by dual culture and CFS diffusion tests. This suggests its potential as a biocontrol agent for damping-off in tomatoes.